Performance Analysis on Road Implementation Project Based on Time and Cost - Alves, Agata Maria Orleans; Tjendani, Hanie Teki; Wulandari, Esti (International Journal of Social Science and Community Service, 2024)
Effective time management is essential for ensuring project implementation aligns with the planned schedule, and one way to achieve this is through the use of Earned Value Analysis (EVA). EVA is employed to estimate the extent to which a project is progressing according to its work plan. This research aims to analyze the timeline of a road construction project using the Earned Value Analysis Method to estimate the final project completion time on a monthly basis. The methodology employed in this study involves the application of the Earned Value Method over a project duration of 18 months. The importance of the Earned Value Analysis Method lies in its ability to assist both the project owner and implementer in more easily analyzing the project's performance, thereby providing significant benefits for both parties. The study found that the project completion time did not align with the initial project schedule. Specifically, the calculation of the cumulative project completion time was 9 months, whereas the planned duration was 18 months. This indicates a delay of 7 months beyond the planned schedule.